Psychomodulatory substances: New legislative framework for control of psychoactive substances in Czechia - Mravčík, Viktor; Michailidu, Jana; Pleva, Petr; Lucký, Matyáš; Kiššová, Lucia; Vobořil, Jindřich (The International journal on drug policy, 2024)
This article challenges drug prohibition advocated by UN conventions as the prevailing regulatory model for psychoactive substances, highlighting its ineffectiveness, harmfulness and outdated nature. At the same time, the conventions exclude some psychoactive substances from international regulation, leaving control to individual countries. Presenting an innovative approach, this article outlines an approach to the legal regulation of psychomodulatory substances (psychoactive substances with low health and societal risk) in non-medical contexts. Acknowledging the potential benefits of such psychoactive substances and balancing them with potential harms, it suggests stringent rules for marketing, safety, and preventing sales to minors. This approach aims to quell illicit markets, safeguard vulnerable populations, and encourage controlled use. Through a case study of the Czech Republic's introduction of a new category of psychomodulatory substances, this article showcases a paradigm shift from the prevailing repressive approach to drug regulation. This adaptive model effectively navigates the regulatory void, offering a viable alternative to the UN's prohibition framework.
Keywords: poruchy spojené s užíváním psychoaktivních látek; Psychotropic Drugs; Drug and Narcotic Control; zakázané drogy; psychotropní léky; Substance-Related Disorders; Humans; Česká republika; zákonodárství lékové; kontrola léčiv a omamných látek; lidé; Legislation, Drug; Illicit Drugs; Czech Republic